Strategy For Enhancing The Attraction Of Situ Cikoncang Tourist Destination Based On Sustainable Tourism (Sustainable Tourism)” District Lebak – Banten - Marsalino, Marsalino; Saripan, Saripan; Dewi, Yoana Amelia; Azizah, Raden Siti; Herfiansyah, M Herlan (Program Pascasarjana Universitas Negeri Makassar, 2025)
Situ Cikoncang in Lebak Regency, Banten has great potential as a sustainable tourism-based destination, but stillfaces challenges in accessibility, community empowerment, and tourism promotion. This research aims toanalyze strategies to enhance the attractiveness of Situ Cikoncang through the 6A component approach:Attraction, Accessibility, Amenities, Ancillary, Activity, and Available Package. The method used is qualitativedescriptive with data collection techniques including observation, in-depth interviews, and documentation, aswell as data validation using source and technique triangulation. The research results indicate that roadimprovements as the main access are a crucial priority to support tourist visits, accompanied by the developmentof additional attractions such as cultural festivals and conservation ecotourism. In addition, the improvement ofsupporting facilities, the establishment of tourist information centers, and the strengthening of Pokdarwiscapacity can enhance services at the destination. Another strategy is the development of integrated tour packagesin collaboration with travel agents and local SMEs to expand the reach of promotions. With the implementationof an integrated strategy involving the government, community, and stakeholders, Situ Cikoncang is expected todevelop into a premier sustainable destination that provides economic and social benefits to the local community.